Culpa(bilidade) : da culpa em psicanálise à culpabilidade no direito penal - Puthin, Sarah Reis (2021)
The present study sought to investigate how behavior according to - or contrary to - culture and the norms of culture is conceived in psychoanalysis, starting from the understanding of the notions of conscience and feeling of guilt and superego in Freudian texts; to then discuss possible psychoanalytic contributions to the science of criminal law, especially with regard to the concept of responsibility in criminal law. Thus, this thesis is constituted by the interface between psychoanalysis and criminal law and, considering the criminal sciences as an explicitly interdisciplinary area of knowledge, it is justified by recognizing the relevance and merit of this approach due to the emphasis on the subject, understanding the subject of the law and the subject of psychoanalysis as distinct constructs, but similar as a subject of culture. Considering the objectives of this research, we firstly sought to understand and elucidate the theoretical development process of psychoanalysis in Freud, in order to support this theoretical-methodological choice and to demonstrate the viability and adequacy of the interface between psychoanalytic theory and criminal law , illustrating how this path has already been followed in the criminal sciences; then, a systematization of the psychoanalytic theory was carried out, with an emphasis on Freudian constructs, in order to build the understanding of the criminal behavior thesis constituted from the idea of guilt in psychoanalysis, exposing the psychoanalytic foundations about the composition of the psyche in psychic instances, the development of guilt feeling and conscience and conditions of insertion of the subject in culture; finally, we sought to reflect on criminal law from the perspective of psychoanalysis, proposing to know and discuss elements of the theory of crime, having as its core the concept of guilt in legal-criminal dogmatics, demonstrating the nexus between guilt in psychoanalysis and responsibility in criminal law . It can be concluded that the understanding of criminal behavior in psychoanalysis runs through the concept of guilt, with the structuring of the superego and the (conscience and feeling of) guilt being relevant elements to understand the subject's conduct in conformity with or contrary to the norms and culture. Starting from this exposed thesis, the link between guilt in psychoanalysis and legal-criminal guilt is glimpsed, regarding psychic conditions of culpability, however it is understood that the inferences allow to go only up to this point, because reinforces the limits imposed in the interdisciplinarity of this study. In this sense, it is worth inferring that the interface between penal sciences and psychoanalysis is relevant to both areas of knowledge, but requires care to the theoretical and methodological limits and interdisciplinary ethics.